Predictors of Money Spent on Drugs in Substance Users - Ciobotaru, Simona (2015)
Financial need is a major stressor for individuals who are reentering the community after substance abuse and/or incarceration. Family members and friends make up a great majority the support networks from which reentering people can receive financial support. However, that financial support could possibly contribute to drug use when the individual is actively using. The goal of this study was to further understand the implications of material and financial support specifically being transmitted from family members. This study looks at psychosocial predictors in relation to money spent on drugs in the last 30 days of 270 individuals entering substance abuse treatment post incarceration and different associated predictors. The results show that the age and addiction severity are significant predictors in monetary amount spent on drugs